Practical immune-barometer sensor for trivalent chromium ion detection using gold core platinum shell nanoparticle probes. Issue 6 (20th February 2018) - Xiao, Meng; Shen, Haicong; Fu, Qiangqiang; Xiao, Wei; Bian, Hongfen; Zhang, Zhigang; Tang, Yong
Abstract : Schematic of an immune-barometer sensor, including a digital barometer and a competitive immunoassay reaction system. Abstract : The technology progress of biosensors has markedly improved healthcare, disease diagnosis, environment monitoring, and food safety control over the past few decades. However, development of sensitive, robust, low-cost and portable assays for on-site bioanalysis is still a great challenge. In this study, we described a portable, feasible and miniaturized immune-barometer sensor (IBS), which can be used to sensitively measure the changes in a pressure signal, and we applied this IBS in the detection of Cr(iii ). In this system, a competitive immunoassay was incorporated as a signaling technique for Cr(iii ) detection. To generate a signal of pressure changes (Δ P ), Au@PtNPs (gold core platinum shell nanoparticles) were prepared for decomposing H2 O2 to generate O2 in a sealed chamber. The expansion of gas volume was accurately detected using a sensitive barometer in the sealed reaction chamber. The Δ P correlated well with Cr(iii ) concentrations ranging from 0.39 to 25 ng mL −1 . The limit of detection (LOD) of the IBS was estimated to be as low as 0.35 ng mL −1 . Furthermore, the IBS has high specificity and high recovery for Cr(iii ) detection in tap water samples (97.5%–108.7%) and in the Pearl River water samples (95.6%–110.2%). Compared with the traditional enzyme-linked immunosorbent assay (ELISA), the IBS was observed to be more sensitive, of low-cost and portable for the on-site detection of Cr(iii ). Therefore, the IBS is a promising potential method for the detection of heavy metals in aqueous solutions and many other fields.